Influencia de la temperatura de síntesis sobre la estructura cristalina y rugosidad de películas delgadas de MoN preparadas por pulverización magnética con corriente continua - De La Cruz Flores, José Luis (2018)
Thin lms of molybdenum (Mo) and Molybdenum Nitride (Mo2N) have properties such_x000D_ as high melting point, high conductivity, good chemical stability and high hardness. Due to_x000D_ their remarkable properties they are of great use in microelectronics, and solar cells. The objective of the study was to determine the e ect of the synthesis temperature on the crystalline structure and the roughness of the thin lms of molybdenum nitride. The Molybdenum and Molybdenum Nitride lms were deposited on silicon substrates of preferential direction (111) type n by means of the direct current reactive magnetron sputtering. For which a pre vacuum was made and then high vacuum, the Argon gas was added, a DC voltage was applied and then the Nitrogen gas with certain pressure parameters, the target was high purity molybdenum and lms were obtained at di erent temperatures during the time of 10 minutes. To know the crystalline structure of the thin lms, an X-ray di ractometer was used and an atomic force microscope was used to determine the roughness. Noting that the crystalline structure does not change with increasing temperature, the roughness of the molybdenum nitride lms decreases from 1.093 nm to 0.602 nm as the temperature increases. Mo2N lms were obtained, where the crystalline structure does not change and the roughness decreased as the temperature increases